Pb concentrations and isotope ratios of soil O and C horizons in Nord-Trøndelag, central Norway: Anthropogenic or natural sources?. (November 2016) - Reimann, C.; Fabian, K.; Flem, B.; Schilling, J.; Roberts, D.; Englmaier, P.
Abstract: Soil O and C horizon samples (N = 752) were collected at a sample density of 1 site/36 km 2 in Nord-Trøndelag and parts of Sør-Trøndelag (c. 25, 000 km 2 ), and analysed for Pb and three of the four naturally occurring Pb isotopes ( 206 Pb, 207 Pb and 208 Pb) in a HNO3 /HCl extraction. Soil O and C horizons are decoupled in terms of both Pb concentrations and Pb isotope ratios. In the soil C horizon the Grong-Olden Culmination, a continuous exposure of the Precambrian crystalline basement across the general grain of the Caledonian orogen, is marked by a distinct 206 Pb/ 207 Pb isotope ratio anomaly. No clear regional or even local patterns are detected when mapping the Pb isotope ratios in the soil O horizon samples. Variation in the isotope ratios declines significantly from the soil C to the O horizon. On average, Pb concentrations in the O horizon are four times higher and the 206 Pb/ 207 Pb isotope ratio is shifted towards a median of 1.15 in comparison to 1.27 in the C horizon. It is demonstrated that natural processes like weathering in combination with plant uptake need to be taken into account in order to distinguish anthropogenic input from natural influences on Pb concentration and the 206 Pb/ 207 Pb isotope ratio in the soil O horizon. Highlights: Lead concentrations are on average higher by a factor of 4 in the soil O than in the C horizon. The 206 Pb/ 207 Pb isotope ratio is considerably lower in the soil O than in the C horizon. The observed shifts are in conflict with exclusive anthropogenic input of Pb. The hypothesis of natural Pb-isotope invariance can not be hold.